Peningkatan pemahaman konsep kegiatan ekonomi dalam pemanfaatan sumber daya alam melalui penerapan model pembelajaran kooperatif tipe talking stick kelas IV sekolah dasar - Rachadiyanti, An Nisha; Mulyono, Hadi; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2020)
The purpose of this research is improving concept comprehension of economic activity in the utilization of natural resource. This research classified into Classroom Action Research using two cycles. There are the subjects are 28 from IV grade students at Mangkuyudan elementary school No.02 in the 2019/2020 academic year. Technique of data collection are interview, tests, observation, and documentation while data analyze technique are quantitative and qualitative. In the first cycle resulting 55% and the second cycle resulting 83,83% in classical terms. The average value is 79,5. Based on the result, it was concluded that the cooperative learning model with talking stick can improve comprehension concept of economic activity in the utilization of natural resource of fourth grade of Mangkuyudan elementary school No.02 in the 2019/2020 and the teacher can apply this model for improving another theory.